Polynuclear Aminohydroximate Metallamacrocyclic Cu(II)‐Ce(III) Complexes: A Facile Route to Intricate Nanostructures of Copper and Cerium Oxides. Issue 7 (30th January 2019) - Katkova, Marina A.; Kremlev, Kirill V.; Zabrodina, Galina S.; Rumyantcev, Roman V.; Gazhulina, Anastasia P.; Gusev, Sergey A.; Ketkov, Sergey Yu.; Fomina, Irina G.; Eremenko, Igor L.
Abstract : With an idea to explore the unique structure of the lanthanide 15‐MC‐5 metallacrowns, the water‐soluble Cu(II)‐Ce(III) aqua‐complexes, bearing aminohydroximate (glycine‐ and α‐phenylalanine) ligands have been synthesized and tested for preparing the target copper and cerium oxides under hydrothermal conditions. These Polynuclear heterometallic metallamacrocyclic complexes represent the unique single‐source precursors for a facile one‐pot, surfactant‐ and template‐free synthesis of nano‐ and mesocrystals with the intrinsic features of rough surfaces, high porosity, single‐crystalline structures and complex morphology. The structure, morphology, and composition of as‐prepared samples have been characterized by means of powder X‐ray diffraction (PXRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and energy‐dispersive spectroscopy (EDS). Our results suggest a very simple chemical route to guide the formation of beautiful self‐assembled nanostructures. Abstract : The phenylalaninehydroximate metallamacrocyclic Cu(II)‐Ce(III) compound shows the unique ability to create intricate nanostructures of copper and cerium oxides